Tracheostomy or Not: Prediction of Prolonged Mechanical Ventilation in Guillain–Barré Syndrome - Walgaard, Christa (Neurocrit Care, 2016)
BACKGROUND: Respiratory insufficiency occurs in 20 % of Guillain–Barré syndrome (GBS) patients, and the duration of mechanical ventilation (MV) ranges widely. We identified predictors of prolonged MV to guide clinical decision-making on tracheostomy. METHODS: We analyzed prospectively collected data from 552 patients with GBS in the context of two clinical trials and three cohort studies in The Netherlands. Potential predictors for prolonged MV, defined as duration of ≥14 days, were considered using crosstabs. Selected predictors were analyzed using Cox regression analysis. RESULTS: On a total of 150 (27 %) patients requiring MV, 106 (71 %) patients needed prolonged MV. The median duration of MV was 28 days (Interquartile Range [IQR] 12–60 days). The strongest observed predictors of prolonged MV were muscle weakness and axonal degeneration or unexcitable nerves on nerve conduction studies. Patients who are unable to lift the arms from the bed (bilateral Medical Research Council [MRC] of deltoid muscles of 0–2) at 1 week after intubation have an 87 % chance to require prolonged MV versus 69 % in patients who are able to lift the arms from the bed (bilateral MRC of deltoid muscles of 3–10). Patients in this last group who had axonal degeneration or unexcitable nerves on nerve conduction studies also have a 90 % chance to require prolonged MV. CONCLUSIONS: Ventilated GBS patients who are unable to lift the arms from the bed and patients who have axonal degeneration or unexcitable nerves at 1 week are at high risk of prolonged MV, and tracheostomy should be considered in these patients.